Sister City Partnership of Bandung and Kawasaki in the Environmental Sector during 2017-2020 - Siregar, Nur Asyifa Salsabila; Syafiq Rizqullah, Muhammad Fawwaz (Journal of Paradiplomacy and City Networks, 2022)
Between 2017 and 2020, Bandung, Indonesia, and Kawasaki, Kanagawa Prefecture, Japan, worked together as part of a sister city collaboration in the environmental sector. Bandung and Kawasaki are sister cities, and their governments have cooperated to address Bandung’s waste management and environmental issues as part of this sister-city collaboration. This study employed an interview and a literature review alongside a descriptive qualitative method to get to the bottom of the research topic. This study also applied the theories of “sister cities” and “city diplomacy” in assessing the findings. The study’s findings revealed that the collaboration helped strengthen Bandung’s human resources and enhance the city’s ability to manage and deal with waste issues. This study also discovered that the partnership ran into problems with finances, the Covid-19 pandemic, the communication process, and the priority given to training initiatives over infrastructure.